Da pesquisa psíquica à ciência psicológica: Estudo das experiências religiosas, parapsicológicas, psíquicas e anômalas - Marques, Stella Maris Souza (2021)
Anomalous experiences (AEs) are psychological experiences characterized by unusual experiences and irregular experiences that constitute the object of study of the so-called “Anomalistic Psychology” (PA). In close proximity and similarities to the AEs are the religious experiences (REs), which are experiences referring to the personal encounter with the sacred and constitute the object of study of “Psychology of Religion” (PR) and also of “Phenomenology of Religion” (FR). These experiences are similar in their ways of experiencing and assigning meanings, despite being different, which has led to certain difficulties in understanding the nuances, distinctions and limits in human daily life, especially in the field of psychological health, where religious and / or spiritual, parapsychological and anomalous, are often understood as symptoms of mental disorders or as identical. Considering the lack of clarity and rigorous conceptual description of the knowledge that involves religious and anomalous experiences, we think that there are certain misunderstandings of understanding, analysis and diagnoses that do not reach with due apodicity and evidence the nature of these experiences and their possible combinations, overlaps. Thereby, this research, based on a theoretical-bibliographic analysis, sought to understand the nature of anomalous experience and religious experience, in the face of several epistemological, conceptual and methodological considerations in the scientific study of religious and anomalous experiences. Accordingly, we come to the conclusion that from the contributions of the phenomenology of religion, we have a greater clarification of the experiences that are characterized by being: psychological, psychopathological, religious, anomalous and paranormal and the possible relationships between them.